Relación del examen radiográfico con la eficacia diagnóstica y la decisión de efectuar o no tratamiento - Eraso, Francisco Eduardo; Tyndall, Donald; Ludlow, John B.; Shugars, Daniel (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Objective: This project is in tended to assess the inDuence of diflerent initial radiological exams in terms 01 diagnostic and treatment decision eHicacy generated for patient case simulations. Material and Methods: A group 01four cases were developed for use as simulations. Two modelities, PAN plus 4 posterior BW’s examination and the FMX (14 periapical and 4 posterior bitewings) were compared. A separate silver standard consensus panel was used as the basis Ior comparing the presence or absence 01 caries, periapical pathology and periodontal disease and another panel Ior the consensus in the decision to treat or not treat. A group of observers examined the cases giving opinions and thresholds on presence or absence 01 disease and another group in the decision to treat (yes-no). A confidence scale (1-5) of disease present and treatment was used. Receiver operating characteristic and treetment decision curves were generated with calculated areas (A) analyzed with Kappa statistics Ior inter-observer reliebility. Fisber’s exact test was used Ior association between the observers. Results: Diflerences in agreement among observers Ior each diagnostic data set; treatment modality and radiographic modality was Iound. No significant difference between the observer’s response and consensus panel was found Ior each diagnostic data set, modality and treetment decision. Complete agreement Ior periodontal treatment decisions between observers and consensus panel was lound. Conclusion: Under the conditions 01 this study a combined radiographic technique such as (PAN+BW) in combination with a clinical examination inlormation is as elfective as the full mouth series (FMX) for diagnostic and treetment planning decisions in patient case simulations. Further research is needed to explore the relationship with clinical practice.